Extracellular Vesicles and Resistance to Anticancer Drugs: A Tumor Skeleton Key for Unhinging Chemotherapies - Pompili, Simona; Vetuschi, Antonella; Sferra, Roberta; Cappariello, Alfredo (Frontiers in Oncology, 2022)
Although surgical procedures and clinical care allow reaching high success in fighting most tumors, cancer is still a formidable foe. Recurrence and metastatisation dampen the patients’ overall survival after the first diagnosis, nevertheless the large knowledge of the molecular bases driving these aspects. Chemoresistance is tightly linked to these features and is mainly responsible for the failure of cancer eradication, leaving patients without a crucial medical strategy. Many pathways have been elucidated to trigger insensitiveness to drugs, generally associated with the promotion of tumor growth, aggressiveness and metastatisation. The main mechanisms reported are the expression of transporter proteins, the induction or mutations of oncogenes and transcription factors, the alteration in genomic or mitochondrial DNA, the triggering of autophagy or epithelial to mesenchymal transition, the acquisition of a stem phenotype, and the activation of tumor microenvironment cells. Extracellular Vesicles (EVs) can directly transfer or epigenetically induce to a target cell the molecular machinery responsible for the acquisition of resistance to drugs. In this review, we resume the main body of knowledge supporting the crucial role of EVs in the context of chemoresistance, with particular emphasis on mechanisms related to some of the main drugs used to fight cancer.